Skill Reinforcement Management of Inclusive Education towards Shadow Teachers in Islamic Institutions - Binti Su'aidah Hanur; Giska Enny Fauziah; Fatimah Fatimah; Rismalia Sari (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Inclusive education is not adequately implemented due to a lack of special education teachers in each school unit. This study employs a descriptive qualitative method approach. The analysis is carried out utilizing an ethnographic study approach. The participants in this study are all Shadow Teachers who are receiving training on how to assist special needs students. Data is gathered by interviews, observations, and documentation. The study concludes that there are several stages that must be completed in order to become a Shadow Teacher, including providing initial insight into inclusive schools and types of children with special needs, screening assistance, how to analyze screening results, how to implement learning adjusted to the identified barriers, and how to provide assessments that reflect the abilities that learners have not yet achieved.